2014
DOI: 10.3109/10717544.2014.991952
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and ocular pharmacokinetics of hyaluronan acid-modified mucoadhesive liposomes

Abstract: The aim of this research was to formulate a liposomal preparation of DOX to be applied topically, and to investigate the in vitro and in vivo performance of the prepared liposomes. DOX liposomes were prepared by the solvent evaporation method, and then modified with bioadhesive material HA. Through MTT assay, we found that the safe concentration of liposomes delivered would hit 1 mg/mL. Cellular uptake studies showed that DOX liposomes coated with HA are much more targetable to cell nucleus. Their ocular pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…Although, there was no significant difference in C max of EP between F8 and DV-AqS, AUC 0-12h and AUC 0-inf of F8 and DV-AqH were found to have significant differences. This discrepancy can be explained on the basis of MRT and clearance of F8 as compared to DV-AqS ( Endrenyi et al, 1991 , Lin et al, 2016 ). Despite the fact of being same drainage rate and tear turn over, around 2.1-fold higher MRT of F8 indicated its prolonged retention on ocular surfaces, which provided prolonged ocular absorption of the drug from F8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, there was no significant difference in C max of EP between F8 and DV-AqS, AUC 0-12h and AUC 0-inf of F8 and DV-AqH were found to have significant differences. This discrepancy can be explained on the basis of MRT and clearance of F8 as compared to DV-AqS ( Endrenyi et al, 1991 , Lin et al, 2016 ). Despite the fact of being same drainage rate and tear turn over, around 2.1-fold higher MRT of F8 indicated its prolonged retention on ocular surfaces, which provided prolonged ocular absorption of the drug from F8.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact of being same drainage rate and tear turn over, around 2.1-fold higher MRT of F8 indicated its prolonged retention on ocular surfaces, which provided prolonged ocular absorption of the drug from F8. Moreover, 2.8-times faster clearance (Cl/F) of DV-AqS as compared to F8, indicated that the absorption phase of both were almost similar to reach an approximately same C max , but the elimination of the drug from F8 was around 2.8-times slower than that occurred from DV-AqS ( Endrenyi et al, 1991 , Lin et al, 2016 ), that too supported from the measured concentration of EP, which was well detected even at 12 h, indicating the adherence of F8 on ocular surfaces and slower uptake of EP by the ocular tissues. On other hand, the administered DV-AqS was almost eliminated at 6 h and very small concentration (4.1 ng/mL) of EP was detected at 12 h, which was also explained in previous report ( Kang Derwent and Mieler, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…After 10 min, the turnover rates of the 0.1% FHA, 0.1% HA and saline solutions were 8.1%/min, 21.6%/ min, and 31.0%/min, respectively, demonstrating that HA has a prolonged retention time on the ocular surface. Fluorescence assays have applied doxorubicin due to its intrinsic fluorescence to deliver drugs, including liposomal formulations [ 63 ], mucoadhesive polymers [ 64 ] and active drugs, such as timolol [ 65 ], and these studies have achieved results consistent with those obtained using gamma scintigraphy and active drug determinations. Finally, the results of our in vitro binding experiments aimed at exploring Na-HA CRT are in line with and showed similar periods to FHA studies and showed that Na-HA was superior to the buffer controls.…”
Section: Discussionmentioning
confidence: 99%
“…J o u r n a l P r e -p r o o f More recently, HA has also been combined with lipidic NPs to deliver moxifloxacin [115], tacrolimus [116] and doxorubicin [117]. Due to the ability of HA to target CD44 receptor on the corneal epithelial cells, these studies demonstrated an increase of drug bioavailability without significant toxicity.…”
Section: 2polymeric/lipidic Nanoparticlesmentioning
confidence: 99%